Noise Analysis and Modulation Optimization for Nonlinear Visible Light Communication System With Signal-Dependent Noise - Jiaqi Wei; Yuan Wang; Chen Gong; Nuo Huang (IEEE Photonics Journal, 2023)
This article investigates the characteristics of the signal-dependent noise (SDN) and corresponding modulation design in nonlinear visible light communication (VLC) systems. We first provide the noise model including SDN and signal-independent noise (SIDN) components. Then, we conduct three groups of comparative experiments to explore the noise characteristics in real VLC systems. Experimental results show that the dominance of SDN or SIDN is related to the linearity of VLC system. In a highly linear VLC system, the noise significantly increases with the signal strength. While in a VLC system with nonlinear devices, large nonlinear noise may make SDN less obvious. Based on the experimental results, a modulation optimization method is proposed for the VLC system with SDN. The symbol error rate (SER) of the optimized modulation is much lower than that of the uniform modulation in flat channel. Furthermore, we explore the effect of SDN on linear minimum mean square error (LMMSE) equalization. Simulation results show that the root mean square error of symbol estimation adopting LMMSE equalization is positively correlated with the modulation level. Moreover, the optimized modulation also outperforms the uniform modulation in the inter-symbol interference channel.